1975
DOI: 10.1042/bj1470549
|View full text |Cite
|
Sign up to set email alerts
|

Acyl intermediates in penicillopepsin-catalysed reactions and a discussion of the mechanism of action of pepsins.

Abstract: Penicillopepsin catalyses transpeptidation reactions involving the transfer of the N-terminal amino acids of suitable substrates via covalent acyl intermediates to acceptor peptides, usually the substrate. The major products obtained when Phe-Tyr-Thr-Pro-Lys-Ala and Met-Leu-Gly were used as substrates were Phe-Phe and Met-Met respectively. With Met-Leu-Gly the tetrapeptide Met-Met-Leu-Gly was observed as probable intermediate. Co-incubation of Leu-Tyr-Leu and Phe-Tyr-Thr-Pro-Lys-Ala led to the formation of Leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Finally, conformational changes that involve the flap region ofthe molecule can begin to explain the acyl and amino transfers (24,28,29) that occur in transpeptidation reactions. Covalent intermediates are not likely in the aspartyl proteinase mechanism (7,14,15).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, conformational changes that involve the flap region ofthe molecule can begin to explain the acyl and amino transfers (24,28,29) that occur in transpeptidation reactions. Covalent intermediates are not likely in the aspartyl proteinase mechanism (7,14,15).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of reaction products by high-voltage electrophoresis. The reaction mixtures were separated as described previously (Takahashi & Hofmann, 1975) by high-voltage electrophoresis on Whatman 3MM paper in volatile buffer (pyridine/acetic acid/ water, 1:10:89, by vol.) at pH 3.6 (Bennett, 1967) and Methyl Green was added as a marker (Stevenson, 1971).…”
Section: Methodsmentioning
confidence: 99%
“…We have described (Takahashi et al, 1974;Takahashi & Hofmann, 1975) some initial studies of the action of pig pepsin and penicillopepsin on small substrates. We showed that the enzymes catalysed transpeptidation reactions that involved the transfer of an N-terminal amino acid via a covalent acyl intermediate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that acyl-enzyme intermediates are involved in pepsin catalysis has been raised anew, however, by the finding that porcine pepsin and penicillopepsin catalyze the transfer of the N-terminal leucyl residue of Leu-Tyr-Leu and Leu-Tyr-NH, to the substrate to form chromatographically detectable amounts of the Leu-Leu-Tyr-X products, which are then predominantly cleaved to yield Leu-Leu (30,89), as shown in the reactions below. The report that the action of pepsin on…”
Section: Is There An Acyl-enzyme Intermediate?mentioning
confidence: 99%